2018
DOI: 10.3390/ijms19102980
|View full text |Cite
|
Sign up to set email alerts
|

MiR-205 Mediated Cu-Induced Lipid Accumulation in Yellow Catfish Pelteobagrus fulvidraco

Abstract: The present working hypothesis is that the Cu-induced changes in lipid metabolism may be mediated by miRNAs. Here, we describe the miRNA profile of the liver tissues of yellow catfish exposed to waterborne Cu, based on larger-scale sequencing of small RNA libraries. We identified a total of 172 distinct miRNAs. Among these miRNAs, compared to the control, mRNA expression levels of 16 miRNAs (miR-203a, 205, 1788-3p, 375, 31, 196a, 203b-3p, 2187-5p, 196d, 459-3p, 153a and miR-725, and two novel-miRNAs: chr4-1432… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…3,16 Studies pointed out that single Cu and Zn exposure influenced lipid deposition and metabolism in mammals 17,18 and fish. 1,19,20 The dysfunction of lipid metabolism adversely affects growth performance, reproduction, movement, and migration of aquatic organisms. 21 However, Cu and Zn coexist in the waters, which leads to combined exposure and joint toxicity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3,16 Studies pointed out that single Cu and Zn exposure influenced lipid deposition and metabolism in mammals 17,18 and fish. 1,19,20 The dysfunction of lipid metabolism adversely affects growth performance, reproduction, movement, and migration of aquatic organisms. 21 However, Cu and Zn coexist in the waters, which leads to combined exposure and joint toxicity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Accumulating evidences have shown that miRNAs are implicated in the lipid metabolism [ 14 , 15 , 24 ], suggesting that miRNAs may be a novel therapeutic target to fatty livers. Thus, it is rather crucial to identify novel miRNAs that target key nodes of lipid metabolism and explore their regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs inhibit translation or degradation of target genes by base-pairing to the 3′-UTR of target mRNAs [ 11 , 12 ]. Evidences show that miRNAs are implicated in many physiological and pathological processes of fatty liver diseases [ 12 ] and act as key regulators in lipid metabolism [ 13 , 14 , 15 ]. Thus, miRNAs may be a novel therapeutic target to ameliorate fatty liver diseases.…”
Section: Introductionmentioning
confidence: 99%
“…We speculated that it may be because increased SREBP-1 protein expression was not enough to up-regulate mRNA expression of its target genes fas and scd1. It is well reported that some miR regulate the expression of target genes involved in lipid metabolism (15) . Recently, in mammals, Ru et al reported that SREBP-1 transcriptionally activated specific SRE motifs on the promoter of miR-29, and then miR-29 inversely suppressed SREBP-1 expression by binding to their 3 0 UTR region (16) .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA (miR) are a class of small non-coding RNAs that regulate gene expression post-transcriptionally by binding to the complementary regions in the 3 0 UTR of target mRNAs, resulting in mRNA degradation or attenuated translation (14) . Studies have shown that miR play a role in TAG homeostasis (15) . Recently, Ru et al reported that SREBP-1 can activate miR-29 expression and in turn miR-29 inhibited srebp-1 expression, which unravelled a negative feedback loop mediated by miR-29 in SREBP-1 signalling (16) .…”
mentioning
confidence: 99%